2014
DOI: 10.5897/ajmr2013.6506
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and characterization of microbial communities in Chrysoperla zastrowi sillemi, an important predator of sap sucking insect pests

Abstract: Common green lacewing, Chrysoperla zastrowi sillemi is one of the important biological control agents and is used effectively to manage various insect pests. Chrysopid predators are found to harbor many endosymbiotic yeasts and bacteria. Keeping this in view, a study on the distribution of yeast and bacteria in the adult diverticulum and larval gut was conducted using transmission electron microscopy (TEM) and molecular techniques. TEM showed the presence of a load of bacterial cells towards the periphery of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Recently, Enterobacter spp. and yeast symbionts associated with green lacewing adults and larvae could be identified (Woolfolk and Inglis, 2004 ; Hemalatha et al, 2014 ). Therefore, studying the possible implication of the microflora of C. carnea larvae on crops may offer novel insights into the interaction between this predator species and plant metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Enterobacter spp. and yeast symbionts associated with green lacewing adults and larvae could be identified (Woolfolk and Inglis, 2004 ; Hemalatha et al, 2014 ). Therefore, studying the possible implication of the microflora of C. carnea larvae on crops may offer novel insights into the interaction between this predator species and plant metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PGPB might already be associated with predators such as C. carnea . Baumann showed that insects are associated with prokaryotic endosymbionts, and Hemalatha et al . identified bacteria from B. subtilis and Enterobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…shows a significant difference between fruits from plants treated with 0.05 mol L −1 NaCl as a control (con, grey circles) and fruits from plants treated with 10 8 CFU mL −1 K. radicincitans cells (K.r., black circles). The statistical analysis was performed by MPP using a fold change ≥ 2 and t test P = 0.05, n = 3. prokaryotic endosymbionts, and Hemalatha et al 63 identified bacteria from B. subtilis and Enterobacter spp. in the gut of chrysopid predators.…”
Section: Effect Of K Radicincitans On Fruit Metabolite Profiles Aminmentioning
confidence: 99%
“…Rodolia cardinalis Mulsant (Coleoptera: Coccinellidae) released to control, I. purchase, by (Causton et al 2006;Causton 2009 andCalderon Alvarez et al 2012). C. carnea predator had ability to control insects like coccidis, mealybug, psyllid, thirps, whiteflies and aphids on various crops (Hemalatha et al, 2014). Therefore, the aims of the current study were to evaluate the release of second instar larvae of C. carnea and C. undecimpinctata against I. purchasi under field condition.…”
Section: Iceryamentioning
confidence: 99%